Identification of Distinct Inflammatory Programs and Biomarkers in Systemic Juvenile Idiopathic Arthritis and Related Lung Disease by Serum Proteome Analysis. Issue 7 (31st May 2022) - Chen, Guangbo; Deutsch, Gail H.; Schulert, Grant S.; Zheng, Hong; Jang, SoRi; Trapnell, Bruce; Lee, Pui Y.; Macaubas, Claudia; Ho, Katherine; Schneider, Corinne; Saper, Vivian E.; de Jesus, Adriana Almeida; et al.
Abstract : Objective: Recent observations in systemic juvenile idiopathic arthritis (JIA) suggest an increasing incidence of high‐mortality interstitial lung disease often characterized by a variant of pulmonary alveolar proteinosis (PAP). Co‐occurrence of macrophage activation syndrome (MAS) and PAP in systemic JIA suggests a shared pathology, but patients with lung disease associated with systemic JIA (designated SJIA‐LD) also commonly experience features of drug reaction such as atypical rashes and eosinophilia. This study was undertaken to investigate immunopathology and identify biomarkers in systemic JIA, MAS, and SJIA‐LD. Methods: We used SOMAscan to measure 1, 300 analytes in sera from healthy controls and patients with systemic JIA, MAS, SJIA‐LD, or other related diseases. We verified selected findings by enzyme‐linked immunosorbent assay and lung immunostaining. Because the proteome of a sample may reflect multiple states (systemic JIA, MAS, or SJIA‐LD), we used regression modeling to identify subsets of altered proteins associated with each state. We tested key findings in a validation cohort. Results: Proteome alterations in active systemic JIA and MAS overlapped substantially, including known systemic JIA biomarkers such as serum amyloid A and S100A9, and novel elevations in the levels of heat‐shock proteins and glycolytic enzymes. Interleukin‐18 levels were elevated in all systemic JIA groups, particularly MAS and SJIA‐LD. We also identified an MAS‐independent SJIA‐LD signature notable for elevated levels of intercellular adhesion molecule 5 (ICAM‐5), matrix metalloproteinase 7 (MMP‐7), and allergic/eosinophilic chemokines, which have been previously associated with lung damage. Immunohistochemistry localized ICAM‐5 and MMP‐7 in the lungs of patients with SJIA‐LD. The ability of ICAM‐5 to distinguish SJIA‐LD from systemic JIA/MAS was independently validated. Conclusion: Serum proteins support a systemic JIA–to‐MAS continuum; help distinguish systemic JIA, systemic JIA/MAS, and SJIA‐LD; and suggest etiologic hypotheses. Select biomarkers, such as ICAM‐5, could aid in early detection and management of SJIA‐LD.